2010
DOI: 10.1016/j.actpsy.2010.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Orienting of attention with eye and arrow cues and the effect of overtraining

Abstract: a b s t r a c t a r t i c l e i n f oIn contrast to the classical distinction between a controlled orienting of attention induced by central cues and an automatic capture induced by peripheral cues, recent studies suggest that central cues, such as eyes and arrows, may trigger a reflexive-like attentional shift. Yet, it is not clear if the attention shifts induced by these two cues are similar or if they differ in some important aspect. To answer this question, in Experiment 1 we directly compared eye and arro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 47 publications
2
50
2
1
Order By: Relevance
“…The model predicts that any overlearned cue-target association can become encoded as a schema, and thus show the same pattern of results as gaze cueing. This prediction is consistent with the well-established finding that arrow cues trigger attention shifts that are behaviorally similar to those triggered by gaze cues (Ristic, Friesen, & Kingstone, 2002;Stevens, West, Al-Aidroos, Weger, & Pratt, 2008;Tipples, 2002), and recent evidence that overtraining any arbitrary association between stimulus property and spatial location can produce rapid, involuntary shifts of attention (Guzzon, Brignani, Miniussi, & Marzi, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…The model predicts that any overlearned cue-target association can become encoded as a schema, and thus show the same pattern of results as gaze cueing. This prediction is consistent with the well-established finding that arrow cues trigger attention shifts that are behaviorally similar to those triggered by gaze cues (Ristic, Friesen, & Kingstone, 2002;Stevens, West, Al-Aidroos, Weger, & Pratt, 2008;Tipples, 2002), and recent evidence that overtraining any arbitrary association between stimulus property and spatial location can produce rapid, involuntary shifts of attention (Guzzon, Brignani, Miniussi, & Marzi, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…One alternative may be that a minimum time is required for perceptual processing of the cue. Previous research has demonstrated that arrow precues can shift attention in as little as 100 ms after cue onset (Guzzon et al, 2010;Tipples, 2002). This means that our shortest second delay duration of 100 ms provided adequate time (200 ms total after cue onset) for cue processing.…”
Section: Discussionmentioning
confidence: 75%
“…However, the second delay durations were chosen to optimize the likelihood of observing an eccentricity effect. The times were selected on the basis of previously reported attentional shift times for perceptual (Guzzon et al, 2010;Tipples, 2002;Tsal, 1983) and internal (Experiments 1 and 2; Becker et al, 2000) attention. Furthermore, if performance was modulated by item proximity to fixation or grouping effects, it seems reasonable to expect that these benefits would similarly influence both the pre-and retro-cue conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stimulus onset asynchrony (SOA) between the target and the cue was 200 ms. Subsequently, a target object (face or scrambled face) was presented at the left or right side of the screen for 300 ms. To avoid any differential influence of disengagement from gaze and arrow cues, in this study we used an experimental design comparable with previous studies (Brignani, Guzzon, Marzi, & Miniussi, 2009;Guzzon, Brignani, Miniussi, & Marzi, 2010) whereby the gaze or arrow cue was removed before a target stimulus appeared on the display. The experiment was designed as a localization task.…”
Section: Design and Proceduresmentioning
confidence: 99%